USING YOUTOBE VIDEOS TO IMPROVE STUDENT'S READING COMPREHENSION IN ONLINE LEARNING MODEL IN FIRST MIDDLE SCHOOL - Rahmawati, Rahmawati; Br Simanungkalit, Olga Yulita Sari (Jurnal Bahasa Indonesia Prima (BIP), 2021)
ABSTRACT-In improving students' reading comprehension in online learning, it can be done by using the social media YouTube. The use of YouTube to encourage students' enthusiasm for learning during a pandemic can be a solution for the world of education so that it can continue and develop. This study aims to determine the benefits of using Youtube and the obstacles that occur in the use of Youtube in online learning in improving students' reading comprehension in the online learning model in junior high schools. The results of this study indicate that in improving reading comprehension in learning using this youtube video, it has a positive impact on the student learning process during the pandemic. The benefits provided by learning from YouTube are:improve students' understanding in understanding the material provided, the learning provided becomes more flexible, familiar with technological developments through online learning, and increasing student creativity in learning.the slow internet connection in the students and teachers' areas of residence, the small specifications or performance of the cellphones used by students, the large amount of quota required to access YouTube, and the high price of internet quotas, limited access to computers and smartphones. The solution in overcoming obstacles in online learning is that students will be directed to open the video provided via the video link in the WhatsApp Group directly without switching to the YouTube application even though with a lack of time it takes a little longer but this can overcome the use of internet quota because WhatsApp is included. into the e-learning quota.